Jornalismo como agente de construção da imagem pública: o governo de Flávio Dino nos editoriais do jornal "O Estado do Maranhão" durante o ano eleitoral de 2018 - Sousa, Suzete Gaia de (2021)
This study proposes an analysis of the constructed image of the Flávio Dino government through, specifically, the editorials of the printed newspaper O Estado do Maranhão. The observation period is the electoral race year 2018 - January 1 to December 31. The analysis comprises a space of the journalistic vehicle in which there is a declared position, different from what is expected in terms of news content. For the research, the quantitative Content Analysis (AC) methodology was used to survey the texts that mention Dino, Flávio Dino, State Government, Maranhão and PCdoB. The corpus comprises 85 pieces published during the period of analysis. For data analysis, the software Statistical Package for the Social Sciences (SPSS) and Iramuteq were used. Among the main results of this research, we can mention the newspaper's preference for the thematic economy, which indicates an attempt by the newspaper to guide the public debate because this is a topic capable of causing dissatisfaction on State issues. It was also noticed the predominance of negative editorials and the use of the term communist, in the narrative about Flávio Dino to reinforce an anti-communist perception and opposition to Dino.